2018
DOI: 10.1186/s13002-017-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

The return of the Iberian lynx to Portugal: local voices

Abstract: BackgroundEthnographic research can help to establish dialog between conservationists and local people in reintroduction areas. Considering that predator reintroductions may cause local resistance, we assessed attitudes of different key actor profiles to the return of the Iberian lynx (Lynx pardinus) to Portugal before reintroduction started in 2015. We aimed to characterize a social context from an ethnoecological perspective, including factors such as local knowledge, perceptions, emotions, and opinions.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…A possible reason explaining positive attitudes toward the return of the Iberian lynx is that cats are species with particular public appeal (Macdonald et al, 2015), although this is something that could be investigated in further research. In addition, the Iberian lynx is likely seen as an emblem by local people in the Iberian peninsula, as it was noticed in Portugal (Lopes‐Fernandez et al, 2018) and also in our study area (authors' unpublished data). Indeed, most participants in our study pointed at the need to preserve the last lynx populations for future generations (Figure 3), suggesting that people may see the conservation of emblematic wildlife species bearers of intrinsic value and representative of common identity and cultural heritage as an obligation (Rode et al, 2021; Smith, 2016).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A possible reason explaining positive attitudes toward the return of the Iberian lynx is that cats are species with particular public appeal (Macdonald et al, 2015), although this is something that could be investigated in further research. In addition, the Iberian lynx is likely seen as an emblem by local people in the Iberian peninsula, as it was noticed in Portugal (Lopes‐Fernandez et al, 2018) and also in our study area (authors' unpublished data). Indeed, most participants in our study pointed at the need to preserve the last lynx populations for future generations (Figure 3), suggesting that people may see the conservation of emblematic wildlife species bearers of intrinsic value and representative of common identity and cultural heritage as an obligation (Rode et al, 2021; Smith, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…Since then, lynx numbers have increased to more than 1000 individuals in 8 populations across central‐southern Iberia (https://www.wwf.es/nuestro_trabajo/especies_y_habitats/lince_iberico/; Figure 1). Between 2012 and 2014, a study conducted following an ethnographic approach showed that key actors were mostly positive about lynx presence in two pre‐selected areas for lynx reintroduction in Portugal (e.g., Lopes‐Fernandez et al, 2018). The primary goal of our research was to compare support toward lynx reintroduction before and after the release of the lynxes in an area of southern Spain where first reintroductions took place.…”
Section: Introductionmentioning
confidence: 99%
“…Negative attitudes towards further population growth among hunters may increase over concern for the effects of lynx on game populations. This has happened in other European countries (see [5,67]). Further increases in lynx abundance may also cause losses to sheep farms (the number of sheep kept in the country was over 150,000 in 2017-2020, [68]).…”
Section: Discussionmentioning
confidence: 87%
“…In Portugal, several ethnobiology studies were published in the past 10 years, ranging from ethnobotany (Carvalho and Fraza ˜o-Moreira, 2011), to ethnoherpetology (Cerı ´aco, 2012), to ethno-ichthyology (Braga et al 2019(Braga et al , 2020, to ethno-malacology (Braga et al 2022), to ethnomammalogy (Lopes-Fernandes et al 2018), even to ethnobiological studies related to ecosystem services (Sousa et al 2013) supporting a growing interest in this area. Stakeholders often participate and contribute to these works, namely fishermen, whose knowledge and perception cover not only commercial fish, but also sharks ecology and coastal management regulations (Barbosa-Filho et al 2014;Liao et al 2019;Morado et al 2021).…”
Section: Introductionmentioning
confidence: 99%